A Local Community Empowerment Model through Green Entrepreneurship in Bandung Regency West Java - Nani Sutarni; Suwatno Suwatno; Hady Siti Hadijah; Hendri Winata; Purnomo Purnomo; Diemas Arya Komara (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop a culturally grounded learning model that integrates Sundanese local wisdom, ecological ethics, and entrepreneurship to strengthen the sustainable management of natural resources within the indigenous community of Kampung Sunda, Desa Laksana, Bandung Regency, West Java. Methodology: A qualitative descriptive–constructive design was employed. Data were collected through in-depth interviews, participant observation, documentation, focus group discussions (FGD), and SWOT analysis with traditional leaders, community members, and local officials selected purposively. Data were analyzed thematically using the Miles and Huberman interactive model and organized through the Standard Model of Indigenous Learning framework. Main Findings: An effective learning model must be anchored in Sundanese cosmology tri tangtu di buana and silih asih, silih asah, silih asuh and enacted through contextual, participatory, active, reflective, and collaborative strategies. Agricultural, forest, water, and biodiversity resources governed through tumpangsari, leuweung titipan, and collective irrigation support ecological enterprises, while ecologized cultural learning, environment-based modules, holistic assessment, and multi-stakeholder collaboration enhance entrepreneurial knowledge and skills. Novelty/Originality of this study: This study integrates cultural, ecological, and entrepreneurial dimensions within a single learning model rooted in a living indigenous tradition, operationalized through the Standard Model of Indigenous Learning. It offers a transferable design for ecopreneurship education in indigenous territories and contributes directly to the achievement of SDG 4, SDG 8, and SDG 15.